Permanent health education in the work process of primary health care nurses - Naiara Martins e Silva Oliveira; Cícero Damon Carvalho de Alencar; José Benedito dos Santos Batista Neto; Ana Cristina Henrique de Souza; José Adelmo da Silva Filho; Heraldo Simões Ferreira; Luisa Helena de Oliveira Lima; Antonio Germane Alves Pinto (Revista de Enfermagem da UFPI)
Objective: To analyze the insertion of the dimensions of the quadrilateral of Permanent Health Education in the work process under the perception of Primary Health Care nurses. Methods: This is an exploratory-descriptive qualitative study carried out in a municipality belonging to the Macroregion of Fortaleza-Ceará. The study sample consisted of 30 nurses working in Primary Care. Data collection took place between November 2019 and February 2020, in which the semi-structured interview script was used and, soon after, the thematic Content Analysis, proposed by Bardin, was carried out. Results: After compiling and analyzing the narratives, they were divided into thematic units, consistent with the dimensions of Permanent Health Education (teaching, sectoral management, health care and social control) in the nurses' work process. Conclusion: Nurses understand the training policy with emphasis on specific, fragmented and decontextualized actions in the context of the service occurring through nurses from several higher education institutions, with no fixed periodicity to happen and no plan for this process.